PENERAPAN CLOUD COMPUTING PADA UMKM WAHYU LAUNDRY - Efa Sa'adah; Yuliati; Dila Rusti; M. Ramli (Digital Business Insights Journal, 2025)
Currently, the laundry business or clothing washing service is continuously evolving. The growth of this business presents new challenges for laundry entrepreneurs due to the increasing competition in this field. This high level of competition has led to decreasing revenue. Therefore, an appropriate strategy is necessary to address these issues, one of which is to maximize service. This research aims to develop a laundry administration system model to improve customer service, to analyze and implement cloud computing technology in Wahyu Laundry, a micro, small, and medium enterprise (MSME), as a digital solution to enhance operational efficiency and data management. MSMEs often face challenges in managing customer information, transactions, and inventory due to limited technological resources.By utilizing cloud services such as online data storage, web-based business management applications, and automated recording systems, Wahyu Laundry can manage its business more effectively and in real-time without relying on expensive local hardware.